Book Review: Eat Right, Feel Right by Leslie Korn (Fourth World Journal, 2025)
This review discusses Dr. Leslie E. Korn’s book Eat Right, Feel Right, which emphasizes the importance of consuming clean, minimally processed foods to support both physical and mental well-being.